Kawasan Kompleks Bangunan Megalitik di Kabupaten Lahat Sebagai Daya Tarik Wisata Budaya dan Alam - Ni Komang Ayu Astiti (Kapata Arkeologi, 2017)
The contribution of tourism to the global economic development continues to increase, affecting the government's policy to make tourism one of the priority sectors of national development after food and maritime. This becomes an opportunity to explore creatively the potential to fill this opportunity. The main question in this research is focus on how the complex area of megalithic building can play an important role in as a resource in national development, especially in the economic sector through tourism. The objective of the study is to restore megalithic complexes from the archaeological context to the social context of today's society as a resource in the development of contemporary times while maintaining its preservation. The method used a qualitative descriptive approach with data collection techniques through direct observation and interview. The results show that this cultural heritage can be a tourism commodity produces products that provide experience in: 1) important historical value; 2) the value of information; 3) aesthetic value; and 4) symbolic value. Strategies used in the management of integrating cultural heritage and the natural environment (landscape), enhancing the role of communities and other stakeholders, maintaining the originality and authenticity of megalithic and landscape buildings, and fostering the desire to invest and community effort. This management is expected to use a conservation approach to cultural and environmental resources as well as community empowerment.Kontribusi pariwisata dalam pembangunan ekonomi secara global terus meningkat, berdampak pada kebijakan pemerintah untuk menjadikan pariwisata sebagai salah satu sektor prioritas pembangunan nasional setelah pangan dan maritim. Hal ini menjadi peluang mengekplorasi secara kreatif potensi yang ada. Permasalahan penelitian dalam tulisan ini adalah bagaimana kawasan kompleks bangunan megalitik dapat berperan penting sebagai sumber daya pembangunan nasional khususnya dalam sektor ekonomi melalui kepariwisataan. Tujuan penelitian tulisan ini untuk mengembalikan kompleks bangunan megalitik dari konteks arkeologi ke konteks sosial masyarakat sekarang sebagai sumber daya dalam pembangunan masa kekinian dengan tetap menjaga pelestariannya. Metode penelitian menggunakan pendekatan kualitatif deskriftif dengan teknik pengumpulan data melalui observasi langsung dan wawancara. Hasil penelitian menunjukan bahwa warisan budaya ini dapat menjadi komoditas pariwisata yang menghasilkan produk yang memberikan pengalaman (experiences) dalam: 1) nilai penting sejarah; 2) nilai informasi; 3) nilai estetika; dan 4) nilai simbolik. Strategi yang digunakan dalam pengelolaan yaitu memadukan warisan budaya dan lingkungan alam, meningkatkan peran masyarakat dan pemangku kepentingan lainnya, mempertahankan originalitas dan otentisitas bangunan megalitik dan lansekap, serta menumbuhkan keinginan untuk berinvestasi dan usaha masyarakat. Pengelolaan ini diharapkan menggunakan pendekatan pelestarian sumber daya budaya dan lingkungan serta pemberdayaan masyarakat.